2004
DOI: 10.1023/b:gene.0000040938.13344.70
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of Casuarinas Using ISSR and FISSR Markers

Abstract: Inter simple sequence repeat polymerase chain reaction (ISSR-PCR) was used for the genetic analysis of the six species of Allocasuarina, five species of Casuarina and 12 superior performing selections of C. equisetifolia L. We also fingerprinted C. equisetifolia L. selections using Fluorescent-ISSR-PCR (FISSR-PCR), an improvised ISSR-PCR assay. The ISSR analysis provided information on the frequency of various simple sequence repeats in the casuarina genome. The di-nucleotide repeats were more common, among wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Extensive studies have already been reported in many tropical trees viz., Pongamia pinnata (Shyam Sundar et al, 2014); Casuarinas (Yasodha and Kathirvel, 2004) ISSR techniques was used to study the genetic structure and relationship between species and populations. Similarly, DNA based ISSR techniques have been successfully utilized in many genera and species of forest trees (Mohapatra and Singhal, 2000) for diversity study.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies have already been reported in many tropical trees viz., Pongamia pinnata (Shyam Sundar et al, 2014); Casuarinas (Yasodha and Kathirvel, 2004) ISSR techniques was used to study the genetic structure and relationship between species and populations. Similarly, DNA based ISSR techniques have been successfully utilized in many genera and species of forest trees (Mohapatra and Singhal, 2000) for diversity study.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion supports the hypothesis that the plantation in this area was probably created in an effort to solve an immediate environmental problem such as windbreaks and sand-shifting control than for genetic variation. High genetic variation in C. equisetifolia provenances was reported by several studies by using morphological and molecular markers alone or in combination (Pinyopusarerk and Williams, 2000;Yasodha et al, 2004;Kamalakannan et al, 2006). Studies based on amplified fragment length polymorphism (AFLP) markers revealed a high genetic variation among provenances of C. equisetifolia (Huang et al, 2008) and other tropical trees such as Moringa oleifera (Muluvi et al, 1999) and Tectona grandis (Shrestha et al, 2005).…”
Section: Genetic Variationmentioning
confidence: 88%
“…Because it is salt and drought tolerant, and fast growing, C. equisetifolia is also used as windbreaks and sand-shifting control in many parts of the world such as on the northern coast of Senegal (9700 ha) and Southern China (30,000 ha) (Mailly et al, 1994;Zhong et al, 2005). Due to its importance, there is a major effort underway focused on selecting and planting elite clones of C. equisetifolia in Australia and India, but the efficiency of this approach requires the genetic characterization of available genetic resources (Yasodha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven ISSR primers were custom synthesized (SigmaAldrich, USA) for the study. The primers were selected based on the earlier report by Yasodha et al (2004) ( Table 4). PCR amplifications were performed in a 10 ll reaction volume containing about 30 ng of template DNA, 1.0 ll 109 PCR buffer (Bangalore Genei Ltd, India), 2.5 mM MgCl 2 , 0.4 mM dNTPs, 100 nM primer and 0.3 U Taq DNA polymerase (Bangalore Genei Ltd, India).…”
Section: Plant Materialsmentioning
confidence: 99%